Sensitivity and rapidity of blood culture bottles in the detection of cornea organ culture media contamination by bacteria and fungi. Issue 12 (1st December 2002) - Thuret, G; Carricajo, A; Chiquet, C; Vautrin, A C; Celle, N; Boureille, M; Acquart, S; Aubert, G; Maugery, J; Gain, P
Abstract : Aims: To test the bactericidal activity of standard organ culture medium, and to compare the sensitivity and rapidity of blood culture bottles with conventional microbiological methods for detection of bacteria and fungi inoculated in a standard cornea organ culture medium. Methods: The bactericidal activity of contaminated standard organ culture medium containing 100 IU/ml penicillin, 0.1 mg/ml streptomycin, and 0.25 μg/ml amphotericin B was evaluated after 48 hours of incubation at 31°C with five inocula of 14 bacteria. Two yeasts ( Candida spp ) and one Aspergillus were also tested. Contaminated media were then inoculated in three blood bottles (aerobic, anaerobic, fungal) placed in a Bactec 9240 automat; three conventional microbiological broths were the control. Changes in colour of organ culture medium and growth on conventional broth were screened daily by visual inspection. The sensitivity and rapidity of detection of contamination were compared between the three methods: blood bottle, conventional, and visual. Results: Organ culture medium eradicated five bacteria irrespective of the starting inoculums: Streptococcus pneumoniae, Branhamella catarrhalis, Escherichia coli, Propionibacterium acnes, and Haemophilus influenzae . For micro-organisms where the medium was ineffective or bactericidal only (methicillin resistant Staphylococcus aureus, methicillin sensitive Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus haemolyticus, Pseudomonas aeruginosa, Acinetobacter baumannii, Bacillus subtilis, Klebsiella pneumoniae, Enterococcus faecalis, Candida albicans, Candida kruzei, Aspergillus fumigatus), the blood bottle, conventional, and visual methods detected microbial growth in 100%, 76.5%, and 70% of cases respectively. Mean detection time using blood bottles was 15.1 hours (SD 13.8, range 2–52). In cases of detection by the blood bottle method and the conventional method, the former was always faster: 95.5% against 65.2% detection within 24 hours (p=0.022) respectively. Conclusions: Blood bottles detect more efficiently and more rapidly a wider range of bacteria and fungi than the conventional microbiological method and the visual inspection of organ culture media.